Emotional intelligence and medicine. Issue 3 (May 2016) - Kirby, Roger
Abstract : 'Emotional intelligence' is currently a buzz phrase in the world of business, where it is regarded as a prerequisite for all those aspiring to a leadership role. Roger Kirby describes what it is and asks how important is it for doctors to have it?